SOD1 Transcriptional and Posttranscriptional Regulation and Its Potential Implications in ALS - Pamela Milani; Stella Gagliardi; Emanuela Cova; Cristina Cereda (Neurology Research International)
Copper-zinc superoxide dismutase (SOD1) is a detoxifying enzyme localized in the cytosol, nucleus, peroxisomes, and mitochondria. The discovery that mutations in SOD1 gene cause a subset of familial amyotrophic lateral sclerosis (FALS) has attracted great attention, and studies to date have been mainly focused on discovering mutations in the coding region and investigation at protein level. Considering that changes in SOD1 mRNA levels have been associated with sporadic ALS (SALS), a molecular understanding of the processes involved in the regulation of SOD1 gene expression could not only unravel novel regulatory pathways that may govern cellular phenotypes and changes in diseases but also might reveal therapeutic targets and treatments. This review seeks to provide an overview of SOD1 gene structure and of the processes through which SOD1 transcription is controlled. Furthermore, we emphasize the importance to focus future researches on investigating posttranscriptional mechanisms and their relevance to ALS.